Economic Liberalisation in Latin America - Angeles-Castro, Gerardo (London Routledge, 2022)
The book explores the process of economic liberalisation in Latin America and revises the transition from the import substitution industrialisation model to the market-oriented reforms. It explains the theoretical foundations of the neoliberal paradigm and the implications of the policies that were labelled as Washington Consensus. The book also incorporates an assessment on the socio-political norms added to the orthodox prescription, the so-called Post-Washington Consensus. The study comprises a general analysis on the subcontinent and on different economic liberalisation paths by looking at four country case studies, Mexico, Brazil, Chile and Uruguay, since the 1980s to recent years. From this approach, the reader can analyse weaknesses and strengths, the socioeconomic performance, and the difficulties that Latin America has presented through the turbulent process of economic liberalisation both in an early stage and over the longer-run, by means of country case studies encompassing the most diverse and representative styles of economic openness in the subcontinent. This allows to identify the challenges the country face and the appropriate policies they can follow to cope with sustained economic growth, poverty reduction and income distribution within an economic openness environment. The study is carried out analysing and contrasting theoretical andThe book explores the process of economic liberalisation in Latin America and revises the transition from the import substitution industrialisation model to the market-oriented reforms. It explains the theoretical foundations of the neoliberal paradigm and the implications of the policies that were labelled as Washington Consensus. The book also incorporates an assessment on the socio-political norms added to the orthodox prescription, the so-called Post-Washington Consensus. The study comprises a general analysis on the subcontinent and on different economic liberalisation paths by looking at four country case studies, Mexico, Brazil, Chile and Uruguay, since the 1980s to recent years. From this approach, the reader can analyse weaknesses and strengths, the socioeconomic performance, and the difficulties that Latin America has presented through the turbulent process of economic liberalisation both in an early stage and over the longer-run, by means of country case studies encompassing the most diverse and representative styles of economic openness in the subcontinent. This allows to identify the challenges the country face and the appropriate policies they can follow to cope with sustained economic growth, poverty reduction and income distribution within an economic openness environment. The study is carried out analysing and contrasting theoretical andempirical perspectives, allowing a broader understanding of the topics. The book is a complementary reading for textbooks, due to the objectivity with which it addresses important and quotidian issues in the region, associating empirical and theoretical topics, and facilitating the understanding of the international political economy of Latin America. It is as well suitable for practitioners and researches, because of the depth it copes with specific topics and the useful analysis it conducts to incorporate policy implication and suggestions to achieve equitable growth in a context of liberal markets
Includes bibliographical references and index
Keywords: Development | Latin America